2013
DOI: 10.1007/s00221-013-3772-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual scaling of visual and inertial cues

Abstract: In the field of motion-based simulation, it was found that a visual amplitude equal to the inertial amplitude does not always provide the best perceived match between visual and inertial motion. This result is thought to be caused by the "quality" of the motion cues delivered by the simulator motion and visual systems. This paper studies how different visual characteristics, like field of view (FoV) and size and depth cues, influence the scaling between visual and inertial motion in a simulation environment. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“… Steinicke, Bruder, Jerald, Frenz, & Lappe (2010) report an average PSE of gain=0.96 (accuracy) with approximately 30% increase/decrease in gain needed to detect increased/decreased gain. Correia Grácio et al (2013) also report gains close to unity, but they do not report precision in a manner that is comparable to the present study. In general, we attribute differences in values reported across studies to methodological differences including display device, content of the visual scene, and method used to track head movement and render scene motion contingent on that head movement.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“… Steinicke, Bruder, Jerald, Frenz, & Lappe (2010) report an average PSE of gain=0.96 (accuracy) with approximately 30% increase/decrease in gain needed to detect increased/decreased gain. Correia Grácio et al (2013) also report gains close to unity, but they do not report precision in a manner that is comparable to the present study. In general, we attribute differences in values reported across studies to methodological differences including display device, content of the visual scene, and method used to track head movement and render scene motion contingent on that head movement.…”
Section: Discussioncontrasting
confidence: 61%
“…The studies described above investigated stationarity perception during active yaw head turns with scene-fixed fixation (or uncontrolled fixation, which was presumably scene-fixed). Several studies (for example, Jaekl et al., 2005 ; Steinicke et al, 2010 ; Correia Grácio et al., 2013 ; Teng, Allison, & Wilcox, 2023 ) have investigated other degrees of freedom, meaning roll and pitch as well as linear head movements. Reported values for PSEs and JNDs vary considerably depending on the degree of freedom that is investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By varying the field of view, resolution and depth of the visual scene, Correia Grácio et al. ( 2014 ) found that the optimal gain is strongly affected by the ‘quality’ of the visual cues, with more realistic visual scenes giving GMOs closer to 1.…”
Section: Perception Thresholdsmentioning
confidence: 99%
“…7, was similar. An explanation for this can be that participants are less capable of perceiving longitudinal vehicle acceleration, derived from the changes in velocity observed in the simulator visuals, than they are at extracting vehicle yaw rate from these visuals during curve driving due to differences in the optic flow for these two degrees-of-freedom, as explained in [42]. Less accuracy in the visually perceived vehicle motion results in a larger range of simulator motions still being perceived as congruent.…”
Section: B Specific Findingsmentioning
confidence: 99%